The comparative ethics of artificial-intelligence methods for military applications - Rowe, Neil C. (Frontiers in Big Data, 2022)
Concerns about the ethics of the use of artificial intelligence by militaries have insufficiently 8 addressed the important differences between the methods (algorithms) that such software provides. 9 We discuss these methods and identify key differences that affect their ethical military use, most 10 notably for lethal autonomous systems. We discuss possible mitigations of ethical problems such as 11 sharing decision-making with humans, testing of the software, providing explanations of what is 12 being done, looking for biases, and putting explicit ethics into the software. The best mitigation in 13 many cases is providing of explanations of reasoning and calculations to aid transparency.